Rehabilitation of military related neurotrauma - Yochelson, Michael (Henry Stewart Talks, 2011)
History of the field of rehabilitation in the United States military, How experiences in the military have helped to shape the field of neurorehabilitation, More common types of neurotrauma, including blast injury, Traumatic brain injury which is considered the "signature wound" of the conflicts in Iraq and Afghanistan, Non-pharmacological management of neurotrauma, Pharmacological management of neurotrauma